Deep Tectonic Environment Analysis of the Lingshan Conjugate Earthquake within the Qinzhou Fold Belt, South China: Insights Derived from 3D Resistivity Structure Model - Chunheng Yan; Bin Zhou; Yan Zhan; Xiangyu Sun; Sha Li; Lei Li; Peilan Guo (Remote Sensing, 2024)
The Qinzhou fold belt, situated at the contact zone between the Yangtze and Cathaysia blocks in South China, was affected by the 1936 Lingshan M6¾ earthquake and the 1958 Lingshan M5¾ earthquake, both of which occurred within the conjugate structure. Understanding the deep seismogenic setting and causal mechanism of the Lingshan conjugate earthquake is of great significance for assessing the seismic disaster risk in the region. In this study, we utilized 237 magnetotelluric datasets and employed three-dimensional electromagnetic inversion to characterize the deep-seated three-dimensional resistivity structure of the Qinzhou fold belt and the Lingshan seismic zone. The results reveal that: (1) The NE-trending faults within the Qinzhou fold belt and adjacent areas are classified as trans-crustal faults. The faults exhibit crust-mantle ductile shear zones in their deeper sections, which are essential in governing regional tectonic deformation and seismic activity; (2) The electrical structure of the Qinzhou fold belt is in line with the tectonic characteristics of a composite orogenic belt, having experienced several phases of tectonic modification. The southeastern region is being influenced by mantle-derived magmatic activities originating from the Leiqiong area over a significant distance; (3) In the Lingshan seismic zone, the NE-trending Fangcheng-Lingshan fault is a trans-crustal fault and the NW-trending Zhaixu fault is an intra-crustal fault. The electrical structure pattern “two low, one high” in the zone has a significant impact on the deep tectonic framework of the area and influences the deformation behavior of shallow faults; and (4) The seismogenic structure of the 1936 Lingshan M6¾ earthquake was the Fangcheng-Lingshan fault. The earthquake’s genesis was influenced by the coupling effect of tectonic stress and deep thermal dynamics. The seismogenic structure of the 1958 Lingshan M5¾ earthquake was the Zhaixu fault. The earthquake’s genesis was influenced by tectonic stress and static stress triggering from the 1936 Lingshan M6¾ earthquake. The conjugate rupture mode in the Lingshan seismic zone is influenced by various factors, including differences in physical properties, rheology of deep materials, and the scale and depth of fault development.